Analisis Faktor-faktor yang Mempengaruhi Keberhasilan Program Zakat Produktif dalam Meningkatkan Kesejahteraan Mustahik - Rizki, Rizki Yuliana; Yenni Samri Juliati Nasution; Muhammad Syahbudi (IAIN Langsa, 2023)
The purpose of this study is to analyze what factors affect the welfare of mustahik in managing productive zakat. The independent variables in this study include work ethic, training and mentoring. While the dependent variable is the mustahik's welfare. The population in this study are zakat recipients in the economic program from 2019 to 2021 totaling 52 mustahik who are fostered by Dompet Dhuafa Waspada, so that these 52 mustahik are the samples in the study. In addition, this study collected data using a questionnaire so that it uses multiple linear regression analysis in the data analysis method. The approach used is a quantitative approach. The results of the study show that work ethic, training and mentoring variables simultaneously have a significant effect on mustahik welfare while partially, work ethic does not have a significant effect on mustahik welfare. While training and mentoring partially have a positive and significant effect on the welfare of mustahik. This study is limited to the zakat institution Dompet Dhuafa Waspada Medan. Work ethic is always related to the quality of human resources. Education is a means of improving work ethic, because education can add skills and open one's perspective of thinking. While the age factor can be an obstacle to a person's work ethic. The age that is no longer productive also influences the level of enthusiasm for work ethic. This research provides new insights about the factors that influence success in managing productive zakat.